Differential Effects of Infant Vocalizations on Approach-Avoidance Postural Movements in Mothers - Hiraoka, Daiki; Ooishi, Yuuki; Mugitani, Ryoko; Nomura, Michio (Frontiers in Psychology, 2019)
Infant vocalization plays a pivotal role in communicating infant mood to parents and thereby motivating parenting responses. Although many psychological and neural responses to infant vocalization have been reported, few studies have examined maternal approach-avoidance behavior in response to infant vocalization. Thus, this research sought to determine how infant emotional vocalization affects maternal behavior. Twenty mothers participated in this behavioral study, all of whom had infants of 24 months old or less. In the experiment, they stood on a Balance Board that collected real-time data regarding center of pressure (COP), while listening to a series of infant vocalizations including cry, laugh, and babbling. They then listened to the same vocalizations for a second time and rated their felt emotions in response to each vocalization. The participants demonstrated significant postural movements of approaching in response to cry stimuli or to stimuli regarded as highly urgent. In contrast, they demonstrated postural movement of avoidance in response to laugh vocalization. These findings suggest that parenting behavior in response to infant emotional vocalization is regulated not by the pleasant-unpleasant axis but by the urgency of the stimulus.